SPECTROPHOTOMETRIC APPROACH FOR METRONIDAZOLE ASSAY: METHOD DEVELOPMENT AND VALIDATION IN SOLID DOSAGE FORMS (Eureka Journal of Physical and Chemical Research, 2026)
Objective: This study aims to develop and validate a simple, cost-effective, and rapid UV-spectrophotometric method for the quantitative determination of Metronidazole in both its pure form and pharmaceutical tablet formulations.Methods: The analysis was conducted using 0.1 N NaOH as a solvent. Spectral measurements were performed at a maximum wavelength (λmax) of 320 nm using a Shimadzu UV-1800 spectrophotometer with 1 cm quartz cells. The method was strictly validated according to ICH guidelines. High-purity Metronidazole (>99%, Sigma-Aldrich) served as the standard, while commercial tablets (Cipla) were used for the formulation assay to evaluate the method's practical applicability.Results: The method exhibited excellent linearity over the tested concentration range, with a regression equation of Y=0.0215x+0.0743 and a correlation coefficient (R2) of 0.9935. The percentage recovery ranged from 99.33% to 99.88%, demonstrating high accuracy and no significant interference from common excipients. Precision was confirmed by low relative error values (0.1129% to 1.1226%) for concentrations of 10–25 mg/mL. Both intra-day and inter-day precision remained within acceptable limits (Relative Error < 2%). The Limit of Detection (LOD) and Limit of Quantitation (LOQ) were determined to be 0.3069 μg/mL and 0.6302 μg/mL, respectively, indicating high sensitivity.Conclusion: The developed UV-spectrophotometric technique is accurate, precise, and robust. Its simplicity and reliability make it highly suitable for routine quality control and standard assays of Metronidazole in bulk and pharmaceutical dosage forms.
Keywords: Metronidazole, UV-Visible spectrophotometry, Method validation, ICH guidelines, Pharmaceutical analysis.